Aktivitas Anti-Mycobacterium tuberculosis Kombinasi (-)-Epigallocatechin-Gallate (EGCG) dan Obat Antituberkulosis Lini Pertama - Mirzautika, Anggita; Isnaeni, Isnaeni; Purwanto, Djoko Agus (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2020)
Tuberculosis is a global health problem, and there is even an increase in cases of multidrug-resistant tuberculosis in the world. Therefore, research is needed that can find new anti-tuberculosis drugs (OAT) that are more effective for tuberculosis treatment. In this study, the effect of (-)-epigallocatechin-gallate (EGCG) of tea leaves (Camellia sinensis) combined with the first-line OAT will be observed, in order to find out whether EGCG has anti-tuberculosis activity and can increase the potential of first-line OAT in-vitro. The anti-tuberculosis activity of EGCG was determined by broth dilution method using Middlebrook 7H9 media at concentration of 50, 100, 150, dan 200 ppm, then the potential of first-line OAT before and after combined with the EGCG was observed. The results showed that the activity of EGCG at concentration 50 ppm and 100 ppm could inhibit the Mycobacterium tuberculosis growth by 80%, at concentration 150 ppm by 90%, and at concentration 200 ppm by 100%. First-line OAT activity before combined with EGCG was ≥ 90% at 5 ppm rifampicin, 0.5 ppm isoniazid, 50 ppm pyrazinamide, and 5 ppm ethambutol. Whereas after combined with EGCG, the potential of each drug increased, marked by anti-tuberculosis activity achieved ≥ 90% at lower concentrations, i.e. rifampicin 0.5 ppm, isoniazid 0.25 ppm, pyrazinamide 20 ppm, and ethambutol 2 ppm. These results indicated that the potential of each first-line OAT increases after being combined with EGCG, and EGCG has potentiation effect when combined with those drugs. In conclusion, EGCG can increase the first-line OAT activity